Technical and economic comparison of the use of zeranol plus ivermectin versus ivermectin on cattle in the final stages of fattening, in the poorly drained regions of the Orinoco basin in Casanare, Colombia - Acosta, Sandra; Dalel, Lisette (Spei Domus, 2011)
In this study, carried out in 2010 in the municipality of Paz de Aripori (Casanare) we determined the economic impact and daily weight gain when comparing the use of ivermectin at a 3.15% versus a mix of ivermictin plus zeranol at 1% in mono-dose. We selected commercial Brahman males (n = 112), dividing them into two groups. In the first group (n = 56) we put the final stage animals (> 450 kg) and in the second one (n = 56) the ones still in fattening (between 400 and 450 kg). G1 (n = 31) of those in the final stage group, and G3 (n = 28) in the fattening group where injected with ivermectin. The remaining individuals, G2 (n = 25) from the final stage animals and G4 (n = 28) received zeranol and ivermectin. All groups were weighted at the beginning of the research and three months after administration of the composite. To establish whether there existed statistical differences in the daily weight gain (dwg) we made an Anova (F test). There were no significant differences in dwg between the treated groups; however, difference was significant when comparing the animals in the final stage and fattening groups. The final stage group had a dwg of 465+ 138.2 g/day, higher than the one for the fattening group which was 400 + 146 g/day. We determined that utility after direct costs, contribution margins and association of ivermectin-zeranol, was positive when related to the price of the medication.